Repeated Excessive Exercise Attenuates the Anti-Inflammatory Effects of Exercise in Older Men - Sahl, Ronni E.; Andersen, Peter R.; Gronbaek, Katja; Morville, Thomas H.; Rosenkilde, Mads; Rasmusen, Hanne K.; Poulsen, Steen S.; Prats, Clara; Dela, Flemming; Helge, Jørn W. (Frontiers in Physiology, 2017)
Introduction/Purpose: A number of studies have investigated the effect of training with a moderate exercise dose (3–6 h/weekly) on the inflammatory profile in blood, and the data are inconsistent. Cross-sectional studies indicate a positive effect of physical activity level on inflammation levels and risk of metabolic disease. However, it is not clear whether this may be dose dependent and if very prolonged repeated exercise therefore may be beneficial for low-grade inflammation. Based on this we studied how excessive repeated prolonged exercise influenced low-grade inflammation and adipose tissue anti-inflammatory macrophage content in six older male recreationally trained cyclists. Low-grade inflammation and adipose tissue macrophage content were investigated in six older trained men (age: 61 ± 4 years; VO2peak: 48 ± 2 mL kg−1 min−1) following repeated prolonged exercise. Methods: Cycling was performed daily for 14 days covering in total 2,706 km (1,681 miles). Maximal oxygen uptake (VO2peak) was measured before and after the cycling. Duration and intensity of the exercise were determined from heart rates sampled during cycling. An adipose tissue biopsy from subcutaneous abdominal fat and a blood sample were obtained at rest in the overnight fasted state before and after the cycling. Anti-inflammatory adipose tissue macrophages (ATM) were immunohistochemically stained in cross sectional sections using a CD163 binding antibody. The ATM and adipocyte sizes were analyzed blindly. Results: The cyclists exercised daily for 10 h and 31 ± 37 min and average intensity was 53 ± 1% of VO2peak. Body weight remained unchanged and VO2peak decreased by 6 ± 2% (P = 0.04). Plasma inflammatory cytokines, TNFα and IL-18 remained unchanged, as did hsCRP, but plasma IL-6 increased significantly. CD163 macrophage content remained unchanged, as did adipocyte cell size. The HbA1c was not significantly decreased, but there was a trend (P < 0.07) toward an increased insulin resistance as estimated by the Quicki Index. Conclusion: The regular prolonged exercise did not influence abdominal adipose tissue inflammation, but the higher plasma IL-6 concentration concurrent with a trend toward higher insulin resistance and decreased VO2peak implies that the excessive amount of exercise probably attenuated the possible potential anti-inflammatory effects of exercise.